Pelatihan Kepemimpinan Rohani bagi Jemaat Gereja Iman Harap Kasih (IHAKA): Membangun Generasi Pemimpin KOMSEL yang Berdampak tanpa Latar Belakang Teologi Formal - Samuel Bartolo (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service activity (PKM) was carried out at the Church of Faith, Hope, and Love (IHAKA) with the aim of empowering lay members who do not have a formal theological background but have a desire to serve as Cell Group (KOMSEL) leaders. The method used is a participatory approach based on training and contextual reflection, consisting of three stages: interactive workshops, service reflection, and mentoring. The training is designed to equip participants with basic understanding of spiritual leadership, the ability to communicate the Word, as well as patterns of household worship relevant to the congregation's context. The results of the activity showed an increase in participants' confidence in leading worship, the ability to actively discuss the Word, and the formation of closer service relationships through prayer and shared meals. Post-training mentorship also strengthens participants' commitment to serving with faithfulness and humility. This activity demonstrates that service is not merely a routine activity, but a calling in life that can be carried out by lay congregants through simple yet impactful guidance. This PKM is expected to serve as an initial model for other local churches in nurturing lay ministers in a contextual and sustainable manner.